Rapid and Quantitative Chemical Exchange Saturation Transfer (CEST) Imaging with Magnetic Resonance Fingerprinting (MRF) - Cohen, Ouri (Magn Reson Med, 2018)
PURPOSE: To develop a fast magnetic resonance fingerprinting (MRF) method for quantitative chemical exchange saturation transfer (CEST) imaging. METHODS: We implemented a CEST-MRF method to quantify the chemical exchange rate and volume fraction of the N(α)-amine protons of L-arginine (L-Arg) phantoms and the amide and semi-solid exchangeable protons of in vivo rat brain tissue. L-Arg phantoms were made with different concentrations (25–100 mM) and pH (pH 4–6). The MRF acquisition schedule varied the saturation power randomly for 30 iterations (phantom: 0–6 μT; in vivo: 0–4 μT) with a total acquisition time of ≤2 minutes. The signal trajectories were pattern-matched to a large dictionary of signal trajectories simulated using the Bloch-McConnell equations for different combinations of exchange rate, exchangeable proton volume fraction, and water T1 and T2 relaxation times. RESULTS: The chemical exchange rates of the N(α)-amine protons of L-Arg were significantly (p<0.0001) correlated with the rates measured with the Quantitation of Exchange using Saturation Power method. Similarly, the L-Arg concentrations determined using MRF were significantly (p<0.0001) correlated with the known concentrations. The pH dependence of the exchange rate was well fit (R(2)=0.9186) by a base catalyzed exchange model. The amide proton exchange rate measured in rat brain cortex (34.8±11.7 Hz) was in good agreement with that measured previously with the Water Exchange spectroscopy method (28.6±7.4 Hz). The semi-solid proton volume fraction was elevated in white (12.2±1.7%) compared to gray (8.1±1.1%) matter brain regions in agreement with previous magnetization transfer studies. CONCLUSION: CEST-MRF provides a method for fast, quantitative CEST imaging.